Exploring Motivators And Challenges Of Work Engagement: A Study In One Education Department - Yvette Ordellea, Dewin (Universiti Malaysia Sarawak, (UNIMAS), 2021)
Work engagement is vital in every organization since engaged people perform better than other employees and contribute to higher organizational performance. The purpose of this study is to investigate the significance of work engagement in one education department at the District Education Office at Sibu. The Job-Demands Resources (JD-R) model was adopted in this study. This study was completely designed utilizing the qualitative method, and a case study was adapted. Despite the fact that a limited sample size was used to provide the information required by the researcher, the two specific objectives of the study were also achieved by collecting intriguing data. In order to obtain data, a semi-structured interview was performed with the eighth informant. Purposive sampling was used to acquire all informants. This study addressed some of the factors that drive work engagement, such as their opportunity to acquire new experience, their passion for work, recognition, co-worker support, promotion, on-going learning and a supportive working environment, as well as some of the challenges that SISC+ encounter in the workplace. The study identified several challenges to work engagement, including a lack of facilities, teachers with a bad attitude who are unwilling to adapt, and a lack of coordination owing to a lack of leadership abilities. Besides that, implication and recommendations with all associated parties involved in the study. Finally, the researcher believes that this study will provide a thorough understanding of the study of work engagement.